Peran strategis public relations dalam mengembangkan usaha mikro, kecil, dan menengah pasca Covid-19 - Nisa, Haliza Chafifatun (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to explore the crucial role of micro, small, and medium enterprises (MSMEs) in facing economic challenges, particularly in crisis situations in Indonesia. The research method includes an analysis of MSME legal aspects based on Law Number 20 of 2008, as well as operational strategies for managing stores. The results of the analysis indicate that MSMEs have become the primary choice for individuals who have experienced job terminations from large companies post-crisis. The rapid progress of MSMEs is reflected in the increased number of business units and job opportunities available. During the COVID-19 pandemic, there has been a significant increase in online transactions by MSMEs, indicating their success in adapting to physical restrictions. The analysis also identifies constraints such as product availability and price increases, with solutions such as providing adequate stock and transparent pricing explanations. In this context, product quality and digital transformation are key factors in maintaining the success of MSMEs. Overall, MSMEs play a vital role in the Indonesian economy, and continuous support, both in terms of regulations and business innovation, is essential to ensure the sustainability and positive impact of this sector on the national economy.